Relationship Between Workload, Dual Role Conflict, Work Environment, and Social Support with Work Stress - Dinda Bestari Siahaan; Willia Novita Eka Rini; David Kusmawan (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Researchers found problems regarding work stress on employees at the Kenali Besar Health Center, where it is known that work stress is an imbalance of human resources and demands felt by a person. The study aims to determine the relationship between workload, dual role conflict, physical work environment, and social support with work stress in employees at the Kenali Besar Health Center, Jambi City in 2024. Methods: This type of quantitative research uses a questionnaire from Permenaker No. 5 of 2018 and the NIOSH Generic Job Stress Questionnaire. Civil servants as respondents, with a population of 50 and a sample of 36. Results: Univariate analysis of high job stress 26 (72.2%), low 10 (27.8%). high workload 31 (86.1%), low 5 (13.9%), high dual role conflict 26 (72.2%), low 10 (27.8%), high physical work environment 28 (77.8%), low 8 (22.2%), and high social support 26 (72.2%) and low 10 (27.8%). Bivariate analysis of workload with work stress (p-value=0.023), dual role conflict with work stress (p-value=0.008), physical work environment with work stress (p-value=0.004), and social support with work stress (p-value=0.008). Conclusion: There is a relationship between workload, dual role conflict, physical work environment, social support with work stress in employees at the Kenali Besar Health Center, Jambi City in 2024.